2002
DOI: 10.1038/sj.pcan.4500610
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for prostate cancer: toxicological profile of four HSV-tk transducing adenoviral vectors regulated by different promoters

Abstract: Adenoviral vector delivery of the Herpes simplex virus thymidine kinase (HSVtk) gene in combination with the prodrug ganciclovir (GCV) has been tested in phase I clinical trials for prostate cancer and found to exhibit a satisfactory toxicity profile. We have developed additional adenoviral vectors with differing promoters to optimize the expression profile and in the present study evaluate the potential systemic toxicity of these vectors. Four recombinant adenoviral vectors that express the HSV-tk gene were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…The REIC/Dkk‐3 gene was originally identified at Okayama University (Okayama, Japan) as a tumor suppressor gene whose expression is downregulated in various cancers . We previously developed an adenoviral vector expressing the human REIC/Dkk‐3 gene (Ad‐REIC) and reported that treatment with Ad‐REIC induced cancer‐selective apoptosis, via ER stress as a result of the unfolded protein response, in various cancer cell lines . In order to achieve improved effective therapeutic outcomes, we have developed a new adenoviral vector (Ad‐SGE‐REIC), which was constructed with tandemly arrayed enhancers (hTERT, SV40, and CMV) after the poly A sequence, to enhance the expression of the targeted REIC gene .…”
Section: Discussionmentioning
confidence: 99%
“…The REIC/Dkk‐3 gene was originally identified at Okayama University (Okayama, Japan) as a tumor suppressor gene whose expression is downregulated in various cancers . We previously developed an adenoviral vector expressing the human REIC/Dkk‐3 gene (Ad‐REIC) and reported that treatment with Ad‐REIC induced cancer‐selective apoptosis, via ER stress as a result of the unfolded protein response, in various cancer cell lines . In order to achieve improved effective therapeutic outcomes, we have developed a new adenoviral vector (Ad‐SGE‐REIC), which was constructed with tandemly arrayed enhancers (hTERT, SV40, and CMV) after the poly A sequence, to enhance the expression of the targeted REIC gene .…”
Section: Discussionmentioning
confidence: 99%
“…24 A replication competent adenoviral vector with two cytotoxic genes, HSV-tk and cytosine deaminase, has also been safely administered intraprostatically to 15 patients who also received concurrent systemic prodrug treatment, valganciclovir and 5-fluorocytosine, together with conformal XRT to the prostate. 25 Although intratumorally or intralesionally injected adenoviral vectors have the potential to leak into the systemic circulation, infecting parenchymal organs like liver and spleen, [26][27][28] the limited toxicity in the HSV-tk gene therapy clinical trials suggests that in situ delivery may provide a safe approach.…”
Section: Discussionmentioning
confidence: 99%
“…In order to efficiently control the transgene expression only in target cells, various studies have used different tissue specific promoters [15], [16], [17], [18], [19], [20]. One such promoter is epithelial glycoprotein-2/EpCAM/17-1A (EGP2) promoter which selectively kills the EpCAM over expressing cells in many cancers by restricted expression of TK (thymidine kinase) followed by Ganciclovir (GCV) treatment [21], [22].…”
Section: Introductionmentioning
confidence: 99%